Atomic layer deposition of fcc-FePt nanoparticles on g-C3N4 for magnetically recyclable photocatalysts with enhanced photocatalytic performance. Issue 2 (1st February 2019) - You, Junhua; Guo, Yaozu
Abstract: Graphitic carbon nitride (g-C3 N4 ) was synthesized by a sol-gel method, and fcc-FePt nanoparticles were deposited on g-C3 N4 through atomic layer deposition (ALD). The concentration of fcc-FePt was determined by the number of the deposition cycles. The as-synthesized g-C3 N4 /fcc-FePt composites were characterized by XRD, XPS, and VSM for crystallization, surface chemical states, and magnetic properties. The photocatalytic performance of g-C3 N4 /fcc-FePt was investigated by photocatalytic degradation of RhB under visible light irradiation. After the reaction, the catalyst was successfully separated from the solution by a magnet. Finally, the stability test showed that g-C3 N4 /fcc-FePt had a relatively high stability over degradation.